1983
DOI: 10.1002/jcu.1870110409
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic prenatal diagnosis of type III congenital cystic adenomatoid malformation of lung

Abstract: cystic adenomatoid malformation with anomalous blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The antenatal ultrasound finding of type I CCAML has been reported by others (Garrett et al 1975;Donn et al 1981). Type 111 CCAML in only one lung has been reported (Diwan et al 1983;Cave & Adam 1984). Our case is the first reported case where there was type 111 CCAML with bilateral total involvement of the lungs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The antenatal ultrasound finding of type I CCAML has been reported by others (Garrett et al 1975;Donn et al 1981). Type 111 CCAML in only one lung has been reported (Diwan et al 1983;Cave & Adam 1984). Our case is the first reported case where there was type 111 CCAML with bilateral total involvement of the lungs.…”
Section: Discussionsupporting
confidence: 80%
“…There were fewer than 200 cases of CCAML reported in the literature up to 1984. CCAML has been divided into three types by Stocker et al (1975); the rarest is type 3 and we have found reports of only seven cases (Stocker et al 1977;Miller et al 1980;Oster & Fortune 1978;Diwan et al 1983;Johnson et al 1983;Cave & Adam 1984).…”
Section: Discussionmentioning
confidence: 85%
“…as a mass of cuboidal epithelium-lined, alveolus-hke structures usually producing mediastinal shift. 6 An· other classification separates the anomaly simply into two groups: one with cysts larger than 5 ~m (ma~o; cystic) and one with cysts less than 5 mm (macrocystic). In all types, no matter which classification is used, usually one lobe of the lung is involved, with no predominance of either side.…”
Section: Discussionmentioning
confidence: 99%
“…Echogenic tumors of the lung could correspond to CCAM of type III or to sequestration [6,11,13]. The early diagnosis of CCAM is important since it causes cardio-mediastinal and pulmonary compression and it is responsible for cardiorespiratory distress at birth, associated with a high mortality rate (80%) [16].…”
Section: T H E W I D E S P R E a D U S E O F U L T R A S O U N D In Pmentioning
confidence: 99%